Review of: "Boštjan Kerbler: Dejavniki nasledstva na hribovskih kmetijah v Sloveniji (Factors of Succession on Hill Farms in Slovenia)" - Drozg, Vladimir (Journal for Geography, 2008)
Boštjan Kerbler, a researcher at the Urban Planning Institute of the Republic of Slovenia, has prepared a book edition on a very interesting topic, namely the issue of succession on hill farms. The topic is more than current, as Slovenian agriculture faces a decrease in the number of farms, often precisely because of unregulated succession, which consequently leads to the decay of the traditional agricultural cultural landscape and weakening of the economic power of agriculture. Despite the topicality of the theme, the reason we report on the book in a scientific journal is different; Boštjan Kerbler has prepared an exceptional social geographic study in which he combined a social geographic approach to understanding a special social group of residents with the quantitative method of processing empirical data, making the credibility of the findings much greater and more precise. The very narrowly set topic has been deconstructed to such an extent that a wide range of factors have been revealed, related not only to the problem of succession but to the management (operation) of farms in general. In this sense, the discussion is an important contribution to understanding the structure of the agrarian landscape.